Experimental investigation about the adoption of high reflectance materials on the envelope cladding on a scaled street canyon. (1st September 2021) - Battista, Gabriele; de Lieto Vollaro, Emanuele; Grignaffini, Stefano; Ocłoń, Paweł; Vallati, Andrea
Abstract: In the last years innovative building envelope materials were studied in order to mitigate the urban heat island phenomenon in cities. Among them, cool materials represent a valid solution to achieve this goal. These materials are characterized by high solar reflectance and high thermal emittance. Another way to reduce the urban heat island effect is the adoption of retroreflective materials on the building façades, in order to reduce the amount of solar radiation entrapped within the urban fabric. The retroreflective materials have a particular surface conformation that allows to reflect the solar radiation back in the same direction of the incident radiation. In this case, the temperature of the surfaces inside an urban canyon should have lower values compared with the case with common construction materials. Consequently, also the air temperature inside the urban canyon has low values with significant advantages on outdoor thermal comfort and on building thermal energy demands. In this work the solar reflectance directional dependence was investigated with a Goniophotometer. Furthermore, experimental measurements of retroreflective materials effects on a scaled urban canyon were performed. It was found that the albedo of the RR material increases with the incident angle of the light beam from 38.2% to 42.3% with an angle of 8° and 60° respectively. An increase of the reflected radiation to the sky in the case of the use RR materials despite of a commercial Lambertian paint with same albedo at 8° of incident light beam was evaluated. In particular, the measurement brings to assess a maximum average percentage canyon albedo difference of 2.03%. Highlights: Experimental measurements of retroreflective materials effects on a scaled urban canyon were performed. Spatially directional reflectance of retroreflective materials is measured. Home-made albedometer development and calibration for the use on scaled urban canyon. Measurement of canyon albedo with comparison of retroreflective and commercial materials for external building façades.